2018
DOI: 10.1016/j.fcr.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk management options in maize cropping systems in semi-arid areas of Southern Africa

Abstract: A B S T R A C TAlthough rainfed cropping in semi-arid areas is risky due to frequent droughts and dry spells, planting early with the first rains is often expected to result in yield benefits. We hypothesised that planting early leads to yield benefits if the planting coincides with a mineral N flush at the start of the season but leads to crop failure if there is a false start to the cropping season. The effects of different management options, including tillage (ploughing and ripping), mulch (two levels 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The unfertilized plot showed considerably lower grain density as well as panicle density in 2018, and fertilization is considered important in this area. In addition, the planting date is an important factor for improving crop productivity [41]. In seasonal wetlands, ridge-furrow tillage mitigated the risk of crop loss, and manure and/or additional fertilizer application at around tillering might enhance crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…The unfertilized plot showed considerably lower grain density as well as panicle density in 2018, and fertilization is considered important in this area. In addition, the planting date is an important factor for improving crop productivity [41]. In seasonal wetlands, ridge-furrow tillage mitigated the risk of crop loss, and manure and/or additional fertilizer application at around tillering might enhance crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…However, the costs of these inputs form adoption barriers to farmers, while non-chemical alternatives seem to be suboptimal or not yet well adapted to CA (Thierfelder et al, 2018). Masvaya et al (2018) investigated the best combination of sowing time, tillage, fertilizer and mulch practices for maize under semi-arid conditions in southern Africa. They found that for early planting a combination of reduced tillage, mulch and N-fertilizer reduced the risk of crop failure.…”
Section: A Identifying Conservation Agriculture Adaptations and Complementary Practicesmentioning
confidence: 99%
“…(Village leader, 5 July 2012; ward 17 Gwanda district)Households that highly dependent on dry land cropping are therefore highly vulnerable, mainly due to erratic rainfall and adverse climate events such as drought and flooding, which aggravate vulnerability (Nyamadzawo et al, 2013). According to Masyaya et al (2017, 2018) dryland farming is semi-arid area Zimbabwe is generally risky due to the frequency of droughts and dry spells. Maintaining livelihoods through dry land cropping in the area is very difficult because of unreliable environmental and socio-economic conditions.…”
Section: Livelihood Strategiesmentioning
confidence: 99%
“…Faced with few options, rural people continue practicing dry land cropping such as maize (the staple food crop. Crop production remains an important source of energy and contributes up to 60% of food availability (Masvaya et al, 2018). Dryland cropping occupies about 70% of arable land, with a smaller portion of millet and sorghum devoted for brewing beer and an even smaller proportion of legumes such as groundnuts and cowpeas and other crops such as sunflower and sweet potatoes (QUNO, 2015).…”
Section: Livelihood Strategiesmentioning
confidence: 99%